Pengembangan Tatalaksana Kejang pada Anak terhadap Tenaga Kesehatan di Kabupaten Kediri: Improvement on Childhood Seizure Management among Health Care Providers in Kediri - Gunawan, Prastiya Indra; Noviandi, Riza; Samosir, Sunny Mariana; Setyaningtyas, Arina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Seizures that last more than five minutes are categorised as prolonged seizures and have the potential to become status epilepticus which can cause damage to brain neurons. Prompt and optimal seizure management is associated with better outcomes. Health workers in first-level health facilities are the spearhead of health services. Kediri district is a large area consisting of 37 primary health centers and 2 government hospitals (type B and C) with a distance to the provincial referral hospital of ± 120 km, so it is necessary to develop the knowledge of medical personnel, especially in the management of seizures in children. This activity aims to improve the knowledge and skills of medical personnel on the management of seizures in children, especially those who work in first and second level health facilities in the Kediri District area. The activity method includes two stages, namely online seminars and examination of pediatric seizure patients which is a follow-up to the presentation of material on pediatric seizure management. A total of 134 participants consisting of general practitioners, pediatricians, and midwives attended the online seminar. A total of 50 participants completed 10 pre-test and post-test questionnaires via Google Form. The results of this activity showed an increase in the knowledge of health workers in Kediri Regency on the management of childhood seizures with a pre-test score of 60.8 and post-test 87.0. An increase in score of 43.1% was obtained. The positive results of this evaluation indicate that participants increased their knowledge of pediatric seizure management.